El oro: una materia prima esencial para el mundo - Marchese Morales, Adollfo (2019)
Gold is an inert metal of symbol Au and atomic number 79. Peru is the world's sixth-largest gold producer, and La Libertad is its first producer department of this metal. It is of great importance for jewelers, physicians, and, of course, in economics: gold is of great value to investors as a refuge asset.